Acid‐sensing ion channel 1a is involved in ischaemia/reperfusion induced kidney injury by increasing renal epithelia cell apoptosis. Issue 5 (22nd February 2019) - Song, Nana; Lu, Zhihui; Zhang, Jian; Shi, Yiqin; Ning, Yichun; Chen, Jing; Jin, Shi; Shen, Bo; Fang, Yi; Zou, Jianzhou; Teng, Jie; Chu, Xiang-Ping; et al.
Abstract: Acidic microenvironment is commonly observed in ischaemic tissue. In the kidney, extracellular pH dropped from 7.4 to 6.5 within 10 minutes initiation of ischaemia. Acid‐sensing ion channels (ASICs) can be activated by pH drops from 7.4 to 7.0 or lower and permeates to Ca 2+ entrance. Thus, activation of ASIC1a can mediate the intracellular Ca 2+ accumulation and play crucial roles in apoptosis of cells. However, the role of ASICs in renal ischaemic injury is unclear. The aim of the present study was to test the hypothesis that ischaemia increases renal epithelia cell apoptosis through ASIC1a‐mediated calcium entry. The results show that ASIC1a distributed in the proximal tubule with higher level in the renal tubule ischaemic injury both in vivo and in vitro. In vivo, Injection of ASIC1a inhibitor PcTx‐1 previous to ischaemia/reperfusion (I/R) operation attenuated renal ischaemic injury. In vitro, HK‐2 cells were pre‐treated with PcTx‐1 before hypoxia, the intracellular concentration of Ca 2+, mitochondrial transmembrane potential (∆ψm) and apoptosis was measured. Blocking ASIC1a attenuated I/R induced Ca 2+ overflow, loss of ∆ψm and apoptosis in HK‐2 cells. The results revealed that ASIC1a localized in the proximal tubular and contributed to I/R induced kidney injury. Consequently, targeting the ASIC1a may prove to be a novel strategy for AKI patients.